2021
DOI: 10.1101/2021.09.28.462271
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ex VivoandIn VivoCD46 Receptor Utilization by Species D Human Adenovirus Serotype 26 (HAdV26)

Abstract: Human adenovirus serotype 26 (Ad26) is used as a gene-based vaccine against SARS-CoV-2 and HIV-1. Yet, its primary receptor portfolio remains controversial, potentially including sialic acid, CAR, integrins, and CD46. We and others have shown that Ad26 can use CD46, but these observations were questioned by the inability to co-crystallize Ad26 fiber with CD46. Recent work demonstrated that Ad26 binds CD46 with its hexon protein rather than its fiber. We examined the functional consequences of Ad26 for infectio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The importance of fiber knob binding to receptors was first demonstrated with coxsackievirus AdV receptor (CAR), a high affinity attachment factor for most HAdVs, including canine AdV-2 (CAdV-2) and avian AdV CELO (Soudais et al, 2000), but not for the B, D, and G types (Bergelson et al, 1997;Freimuth et al, 1999;Kirby et al, 2000;Roelvink et al, 1998;Tomko et al, 1997). Species B and D use CD46 (Cupelli et al, 2010;Fleischli et al, 2005Fleischli et al, , 2007Gaggar et al, 2003;Gustafsson et al, 2010;Pache et al, 2008;Persson et al, 2009;Russell, 2004;Sakurai et al, 2006Sakurai et al, , 2007Sirena et al, 2004Sirena et al, , 2005Tuve et al, 2006;Wang, Li, Yumul, et al, 2011;Wang, Yumul, et al, 2013) or desmoglein (DSG)-2 (Hemsath et al, 2022;Trinh et al, 2012;Vassal-Stermann et al, 2019;Wang et al, 2015;Wang, Li, Liu, et al, 2011;Wang, Li, Yumul, et al, 2011;Wang, Yumul, et al, 2013). AdV-D26 has been reported to use CD46 or sialic acid as a receptor through fiber knob or hexon as ligands (Baker, Mundy, et al, 2019;Hemsath et al, 2022;Persson et al, 2021).…”
Section: Receptors Attachment Factors and Facilitatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of fiber knob binding to receptors was first demonstrated with coxsackievirus AdV receptor (CAR), a high affinity attachment factor for most HAdVs, including canine AdV-2 (CAdV-2) and avian AdV CELO (Soudais et al, 2000), but not for the B, D, and G types (Bergelson et al, 1997;Freimuth et al, 1999;Kirby et al, 2000;Roelvink et al, 1998;Tomko et al, 1997). Species B and D use CD46 (Cupelli et al, 2010;Fleischli et al, 2005Fleischli et al, , 2007Gaggar et al, 2003;Gustafsson et al, 2010;Pache et al, 2008;Persson et al, 2009;Russell, 2004;Sakurai et al, 2006Sakurai et al, , 2007Sirena et al, 2004Sirena et al, , 2005Tuve et al, 2006;Wang, Li, Yumul, et al, 2011;Wang, Yumul, et al, 2013) or desmoglein (DSG)-2 (Hemsath et al, 2022;Trinh et al, 2012;Vassal-Stermann et al, 2019;Wang et al, 2015;Wang, Li, Liu, et al, 2011;Wang, Li, Yumul, et al, 2011;Wang, Yumul, et al, 2013). AdV-D26 has been reported to use CD46 or sialic acid as a receptor through fiber knob or hexon as ligands (Baker, Mundy, et al, 2019;Hemsath et al, 2022;Persson et al, 2021).…”
Section: Receptors Attachment Factors and Facilitatorsmentioning
confidence: 99%
“…Species B and D use CD46 (Cupelli et al, 2010;Fleischli et al, 2005Fleischli et al, , 2007Gaggar et al, 2003;Gustafsson et al, 2010;Pache et al, 2008;Persson et al, 2009;Russell, 2004;Sakurai et al, 2006Sakurai et al, , 2007Sirena et al, 2004Sirena et al, , 2005Tuve et al, 2006;Wang, Li, Yumul, et al, 2011;Wang, Yumul, et al, 2013) or desmoglein (DSG)-2 (Hemsath et al, 2022;Trinh et al, 2012;Vassal-Stermann et al, 2019;Wang et al, 2015;Wang, Li, Liu, et al, 2011;Wang, Li, Yumul, et al, 2011;Wang, Yumul, et al, 2013). AdV-D26 has been reported to use CD46 or sialic acid as a receptor through fiber knob or hexon as ligands (Baker, Mundy, et al, 2019;Hemsath et al, 2022;Persson et al, 2021).…”
Section: Receptors Attachment Factors and Facilitatorsmentioning
confidence: 99%
“…There are several reports describing HAdV-D26 receptor/s, with rather ambiguous conclusions. [29][30][31][32][33][34][35][36][37] By using B16F10-CD46 cell clones (murine melanoma cell line stably transfected with CD46) it was reported that adenoviruses from group D, namely HAdV-D26, human adenovirus type 48 (HAdV-D48) and type 49 (HAdV-D49) can use CD46 to facilitate cellular entry. The HAdV vectors from group D, however, appeared less efficient than those from group B at transducing B16F10-CD46 cells.…”
Section: Human Adenovirus Type 26 Basic Biologymentioning
confidence: 99%
“…34 It has been reported that HAdV-D26 can functionally interact with CD46 for in vitro and in vivo infection when CD46 is ectopically expressed in cells or in mice, underlying use of CD46 by HAdV-D26 under certain situations. 35 The more pronounced transduction of CAR-negative cells at high vector doses and upon prolonged incubation suggested that HAdV-D26 more readily enters cells upon binding to alternative receptors, such as integrins. 31 Role of integrins in HAdV-D26 cell entry was examined also by Nestić et al 37 By performing different gainand loss-of-function studies, we found that αvβ3 integrin is required for efficient infection of epithelial cells by HAdV-D26, while CAR and CD46 did not influence the transduction efficiency of HAdV-D26.…”
Section: Human Adenovirus Type 26 Basic Biologymentioning
confidence: 99%
“…As HAdV–CD46 interactions are reportedly low affinity, the level and location of CD46 on the cell surface likely influence the avidity, which should influence whether cells can take up species B HAdVs (Marttila et al., 2005; Trinh et al., 2012). HAdV‐D26, currently used as a vaccine vector due to its low seroprevalence in Europe and North America (Mennechet et al., 2019), interacts with CD46 via hexon (Persson et al., 2021; Hemsath et al., 2022). Of note, CD46 can help deliver species B HAdVs toward vesicular TLR9 in macrophages and DCs (Iacobelli‐Martinez & Nemerow, 2007).…”
Section: Recognized Adv Receptorsmentioning
confidence: 99%